Music as Political Power in Postwar Germany: The Fight for German Reunification through the Voices of East and West German Musicians - Meldrum, Monica (Office of Student Research and Creative Activity, 2018)
When the Second World War ended, Germany embarked on a period of heightened reconstruction. Along with the restoration of bombed buildings and the reestablishment of political systems, the postwar era was a time of rich cultural adaptation as German musicians reinvented themselves and their style. Initially, the evolution of music was impacted by the military occupation in Germany and by American and British musical influences, which inspired German musicians to change their sound. However, the Cold War, which divided Germany, influenced the evolution of music in both parts of postwar Germany. In the West, the increasingly democratized Federal Republic of Germany (FRG) embraced capitalism, which created a freer environment for musicians to express themselves. In contrast, the eastern German Democratic Republic (GDR) became a socialist state, which censored music. My paper surveys how musicians in East and West Germany negotiated the presence of the Iron Curtain through their music. Using case studies of two Eastern musical groups and one Western singer-songwriter, I analyze how musicians challenged the socialist system and the Iron Curtain through their music. Whereas Eastern musicians faced censorship and sometimes persecution as they composed and performed their music, Western musicians aided the fight for freedom in the East by composing political music. As my paper demonstrates, musicians provided a voice for the people of a divided Germany and may even have contributed to the fall of the Iron Curtain.
Keywords: Music--Germany--20th century; Popular music--Germany